Professional competence of the experts of preschool education: the nature, content and structure (Pedagogy of Higher and Secondary Education, 2013)
Aronovа R. S. Professional competence of the experts of preschool education: the nature, content and structure.The article is devoted to the problem of professional competence of preschool education specialists. The sense, the main points and structure of professional competence of preschool education specialist are described. The elements researched allow them to fulfill their professional functions and tasks and to provide them with personal development and growth.
Keywords: professional competence; future specialist; preschool education